Sosialisasi Teknik Pembukuan pada Pelatihan Pengelolaan Keuangan BUMDes di Kecamatan Bontoa: Sosialisasi Teknik Pembukuan pada Pelatihan Pengelolaan Keuangan BUMDes - Rahman Pura; Sufiati Sufiati; Sitti Mispa; Nensi Nensi (ADPERTISI, 2022)
The purpose of this activity is to increase knowledge and skills about financial bookkeeping techniques. The audience of the participants are BUMDes managers, totaling 29 people from 6 BUMDes in Bontoa District. The method of carrying out activities with a participatory approach and method of presenting material in the form of lectures. The steps taken are the presentation of the material by the resource person then followed by a discussion. The results of the activity show that the socialization of financial bookkeeping techniques can increase the knowledge ability of managers in understanding BUMDes financial bookkeeping techniques. Follow-up activities in the form of training and technical guidance related to BUMDes financial bookkeeping, both manually and based on applications.